Concept of Freedom: History and Modern Times - V. A. Slyshchenkov (Теоретическая и прикладная юриспруденция)
The historical discussion of formation of the concept of freedom briefly displays main definitions of freedom, shows interrelations and connections of the concept of freedom with other important notions of the human existence, such as subject, self-realization, law, good, labor, knowledge, otherness. Correct understanding of the phenomenon of freedom implies a principle distinction between law and morality. It is law as a social institute that introduces freedom as such into social life, whereas morality provides only liberation from evil. According to the initial definition freedom is a labor of self-realization. As freedom obtains social reality only in a legal form, the more concrete definition of freedom is as follows: freedom is a balance of man’s rights and duties.